The Institution of Legislative Delegation in the Fields of Economics and Finance. An Overview of the Timeframe 2010-2014 - Ionel Bostan (CES Working Papers, 2015)
According to the Romanian Constitution (Art. 115, paragraph 1), the Government, as a body of the Executive Power, is endowed with attributions belonging to the Legislative function, specific to the Parliament. Thus, we are dealing with what the juridical science calls “legislative delegation”. On this basis, the Government may issue simple ordinances, under a special enabling law and emergency ordinances - in case of special circumstances, which both represent primary normative acts with the power of a law. In this paper we approach the issue of the legislative delegation during the recent five years (2010-2014), focusing on a few aspects relating to the fields of finance and economics.
Keywords: K4; 330; K4